A Phenomenological Study of Theft Recidivism and Law Enforcement Strategies in Tulungagung, Indonesia - Nurchasanah (Supremasi Hukum: Jurnal Kajian Ilmu Hukum, 2025)
Theft recidivism remains a persistent global concern that reflects the complex interaction of socio-economic, psychological, and environmental factors shaping criminal behavior across diverse societies. Similar to global trends observed in the United States, Europe, and Japan, recidivism in Indonesia demonstrates how structural inequality, limited rehabilitation, and weak reintegration frameworks perpetuate repeated offending. Despite these parallels, Indonesian studies have primarily focused on normative legal analyses, offering limited insight into offenders' lived experiences and socio-structural dynamics. Addressing this gap, the present study explores the phenomenology of theft recidivism within the jurisdiction of the Tulungagung Police Department through a qualitative approach using deductive analysis. The findings reveal that economic strain, social disconnection, and institutional shortcomings jointly sustain reoffending behavior. Bronfenbrenner's Ecological Systems Theory shows these factors interact across individual, interpersonal, institutional, community, and policy levels, forming an interdependent framework of recidivism. The Tulungagung Police have localized global best practices by integrating Social Control and Community Policing strategies—combining pre-emptive, preventive, restorative, and rehabilitative measures. Programs such as legal education, neighborhood patrols, restorative justice, and post-release empowerment reflect a shift from punitive deterrence to participatory crime prevention. Theoretically, this study contributes to global criminological discourse by contextualizing ecological and phenomenological insights; practically, it offers a localized, evidence-based model for sustainable desistance in Indonesia.